Evaluation of pre-symptomatic nitisinone treatment on long-term outcomes in Tyrosinemia type 1 patients: a systematic review - Geppert, Julia (Orphanet J Rare Dis, 2017)
BACKGROUND: Tyrosinemia type 1 (TYR1) is a rare autosomal recessive disorder of amino acid metabolism that is fatal without treatment. With medication (nitisinone) and dietary restrictions outcomes are improved. We conducted a systematic review to investigate if treatment with nitisinone following screening provides better long-term outcomes than treatment with nitisinone following symptomatic detection. METHODS: We searched Web of Science, Medline, Pre-Medline, and Embase up to 23rd September 2016 for journal articles comparing clinical outcomes of TYR1 patients receiving earlier versus later nitisinone treatment. Two reviewers independently screened titles and abstracts, assessed full texts, and appraised study quality. Data extraction was performed by a single reviewer and checked by a second. RESULTS: We included seven articles out of 470 unique records identified by our search. The seven articles included four studies (three cohort studies and one cross-sectional study). Study sample sizes ranged from 17 to 148. There is consistent evidence that nitisinone is an effective treatment for TYR1, and some evidence that earlier treatment with nitisinone and dietary restrictions within the first one or 2 months of life is associated with reduced need for liver transplantation, lower rates of renal dysfunction, fewer neurological crises, and fewer, shorter hospital admissions compared to later treatment. However, study quality was moderate to weak, with high risk of confounding and applicability concerns to the screening context. We conducted post hoc analyses to address these issues. Results suggested an association between earlier treatment and fewer liver transplants (earlier treatment: 0% of 10–24 patients; later treatment: 25–60% of 4–15 patients), but no impact on neurological crises. We found no effect of treatment timing on mortality in either the primary or post hoc analyses. Post hoc analyses of other health-related outcomes were not possible because of sample size or reporting. CONCLUSIONS: There is some evidence from observational studies that earlier treatment with nitisinone might be beneficial but this is subject to bias. The applicability of our findings to the screening context or clinical practice is limited as not all early-treated patients were identified by screening and late-treated groups included patients born prior to the availability of nitisinone. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13023-017-0696-z) contains supplementary material, which is available to authorized users.